Complete genome sequence of the carotenoid-producing strain gordonia ajoucoccus A2 - Kwon, Soon Jae; Choi, Yong Jin; Kim, Ju Min; Lee, Pyung Cheon (Microbiology Resource Announcements, 2020)
Gordonia ajoucoccus strain A2, isolated from crude oil-contaminated soils, synthesizes yellow keto-γ-carotene from various n-alkanes as the sole carbon source. Its complete genome sequence consists of a single circular chromosome (5,090,254 bp, 67.3% G+C content). Seven putative genes were identified supporting the proposed keto-γ-carotene pathway of G. ajoucoccus A2.